Pengaruh Pressure, Opportunity, dan Rationalization (Fraud Triangle) Terhadap Financial Statement Fraud - Mega Jenice Olinda; Shinta Ningtiyas Nazar (CV. ITTC INDONESIA, 2025)
Fraud is fraud that occurs in the presentation of financial statements. The aim of the research is to examine the influence of Pressure, Opportunity and Rationalization on financial statement fraud. The type of research used is quantitative research. The data source used is secondary data. Population of non-cyclical consumer sector companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The Purposive Sampling method used in this research resulted in 17 companies with a period of 5 years producing 85 observations. Analysis using Eviews software version 9. The results of this research show that pressure, opportunity and rationalization simultaneously influence financial statement fraud. Pressure partially influences financial statement fraud. Opportunity and Rationalization partially have no effect on financial statement fraud.